Aplicação de um reator anaeróbio de alta eficiência para o tratamento de efluentes de uma microdestilaria de álcool - Weber, Diego Polônia (2012)
During the distillation of alcohol is a residue called vinasse generated with high content of organic matter and high pollution potential. As the largest industry effluent of alcohol, stillage is an ecological problem. Faced with this problem, treatment is necessary. Within the context arises the UASB (upflow anaerobic sludge blanket) Seeking sustainability in the agricultural industry, in addition to treating vinasse, biogas is captured for energy use, and may get an economic return. This study aimed to analyze by means of physical-chemical parameters such as temperature, pH, detention time and hydraulic retention rate of climb, macro-nutrients, COD and qualitative methane generation, the behavior of two reactors, pilot scale, performing a comparative characteristics of effluents from a distillery. Thus was determined the efficiency of reduction of the organic load by analyzing the vinasse obtained from two different sources, amylaceous and saccharide. The reduction of the organic load in the effluent was greater potato reached 95.75%, while the sugar cane reached 81.56% removal of COD, satisfactory results for UASB-type reactors.